SOCIAL HOUSING ALLOCATION IN SCOTLAND: THE ADVERSE SELECTION ISSUES - Mahamood, Nur Medeena; MacGregor, Bryan; Schulz, Rainer; Ab Majid, Rohayu; Wan Rodi, Wan Norhishamuddin (PLANNING MALAYSIA, 2023)
Since the social housing in Scotland is delivered through the public purse, ideally, the social landlords should allocate their stock efficiently to the right recipients. However, a social landlord may occasionally be subjected to adverse selection situations when applicants withhold certain information during the social housing application. Within the information theory spectrum, adverse selection stems from the belief that humans tend to act opportunistically by putting their self-interest first above others’ interest. While there is ample evidence of vast adaptation of the information theory in different fields and sectors, there is still a remaining gap in the information theory application in understanding the actors’ interaction in the social housing sector. By utilising semi- structured interviews with the housing officers from one case study, ten (10) housing officers from the case study in Aberdeen participated to share their views and experience during the pre-allocation stage. Three (3) broad themes were discovered which consist of withholding information, exploiting the loophole in the system and finally, lack of ways in verifying the information. Data has been analysed through a combination of thematic and content analysis. The thematic analysis primarily aims to establish common themes across settings. The content analysis is employed to support the thematic analysis by conducting a textual investigation and subsequently establishing the frequencies of the event shared by the housing officers. The findings yielded some noteworthy results that signified the matters commonly manipulated by the applicants, leading to adverse selection situations during the pre-allocation stage. It produces critical insights on the issues that the social landlord should thoroughly assess during the pre-allocation stage in improving their allocation practice. Predominantly, helping them to meet the right target recipients in the social housing allocation.